A single origin for the widely distributed B chromosomes of the gladiator frog Boana albopunctata - Ferro, Juan M.; Gatto, Kaleb P. [UNESP]; Netto, Flavia; Resquin, Juan J.; Costa, William; Marti, Dardo A.; Lourenco, Luciana B.; Baldo, Diego (Oxford Univ Press, 2023)
B chromosomes are supernumerary elements that have a wide taxonomic distribution among eukaryotes. Although they are dispensable, they can acquire mechanisms to be overrepresented in the next generation and therefore avoid being eliminated. These elements have been discovered in < 2% of the karyotyped anurans. B chromosomes were described for Argentine and Brazilian populations of Boana albopunctata, a Neotropical tree frog widely distributed in the central region of South America. We assessed the distribution of B chromosomes in this species via cytogenetic studies of 365 specimens from Argentina, Brazil and Paraguay. We found that 101 individuals carried B chromosomes, with striking differences in their frequency of occurrence among localities. Our findings might be related to the evolutionary dynamics of these elements. Microdissection and chromosome painting experiments demonstrated sequence similarity between B chromosomes from localities that are > 1000 km apart, showing the most widely distributed B chromosome system known for anurans. The B chromosome system of B. albopunctata might help to fill the general knowledge gap for these elements in anurans compared with other vertebrates.
Keywords: Anura; Hylidae; chromosome evolution; chromosome painting; microdissection; supernumerary chromosome